Sulle rappresentazioni di Benito Mussolini e del fascismo in Sibilla Aleramo - Serena Mercuri (Laboratoire Italien)
Fascism’s totalitarian aspiration does not contemplate the creation of new forms of masculine identity exclusively. In fact, a concept of the “New Woman” accompanies the Nietzschean ides of the “New Man”, in a specular and sometimes opposite form. Fascism, indeed, welcomes and promotes the idea of a female universe made up of good wives and excellent mothers of the Fascist faith, identities created according to the dictates of a canon that is not entirely new but which was subject to a framing that was unprecedented in Italian history and specific to the socio-political system. The Fascist woman is thus essentially subordinate: to men, to husbands, to children, to the duce, to the fatherland. How, then, can the feminist ideas of the turn of the century, the emancipationist discourses of A Woman, Sibilla Aleramo, a European Sibyl, then known to the most important transnational feminist circles, be reconciled with the forms of fascist thought? To explore Sibilla Aleramo’s complex relationship with the regime, this article analyzes the occurrences of Benito Mussolini and fascism in the writer’s texts.